Hybrid MMSE precoding design for multiuser millimeter-wave massive MIMO systems - Raisa, Farah (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Millimeter-wave (mmWave) wireless communication technology is considered as the key enabling technology for the future 5th generation (5G) wireless systems because it has the potential to meet the demand of high data rate, low latency and low energy consumption. Highly improved spectral efficiency is one of the prime requirements of the future wireless networks. However, full-potential of mmWave systems can only be achieved if efficient designing of the system is performed that can overcome the huge path loss issue due to high frequencies of mmWave bands. To upgrade the reliability of the wireless communications, exploitation of Multiple-Input-Multiple-Output (MIMO) systems has become well-known technology for a while. Beamforming gains can be achieved with multiple antenna arrays set at the base station (BS). Precoding is identified as an essential component which can increase the potentiality of MIMO systems. Multiuser precoding can be properly utilized to increase the spectral efficiency of the mmWave systems. Analog beamforming has been utilized previously for the conventional microwave bands, but it is not feasible for high frequency mmWave systems. Full-digital precoding system is also cost-inefficient and hardware complexity is very high for mmWave. So, precoding in both analog and digital domain, known as hybrid precoding, has better efficiency for mmWave systems. This thesis aims at improving the efficiency of a multiuser mmWave system by utilizing the hybrid precoding strategies using both RF and baseband precoding at the base station and only analog combining at the receiver. A modified approach for the hybrid precoding is proposed for a mmWave Massive MIMO systems where a large number of antennas are employed at the BS and the MS. At first, RF beamforming is designed for the single user in order to maximize the signal power and after that, multiuser digital precoder is designed with MMSE precoders to mitigate the inter-user interference. The sum rate of the proposed design has been analyzed under perfect channel conditions, where each mobile station (MS) knows the channel and the base station (BS) knows the effective channels perfectly. Numerical simulation is carried out in MATLAB simulation software and the system sum-rate of the proposed hybrid precoding scheme is compared with single-user rate, analog-only beamforming rate and the sum rate of the hybrid precoding with Zero-Forcing precoder. Simulations with various systems settings indicate that the proposed hybrid precoding scheme outperforms all other multiuser precoding algorithms and achieves the efficiency which is very close to the single-user's rate.